PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Alpi, Chicha Ayu Del; Ulupui, I Gusti Ketut Agung; Sasmi, Aji Ahmadi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study aims to determine the effect of profitability proxied by Return on Assets (ROA) and leverage proxied by Debt to Equity Ratio (DER) on earnings management moderated by Good Corporate Governance (GCG) through managerial ownership in manufacturing companies listed on Indonesian Stock Exchange (IDX) in 2022. This study uses SPSS software to process data using multiple linear regression analysis and Moderated Regression Analysis (MRA). The population in this study are manufacturing companies listed on the IDX in 2022 with a total of 308 companies and using these 103 companies as samples through a purposive sampling technique. The results of this study state that profitability and leverage have a positive and significant effect on earnings management. Meanwhile, GCG does not have a significant effect on earnings management and cannot moderate the effect of profitability and leverage on earnings management